Musical Illustration in the Film Silogui: A Cinematic Study of Mentawai Children - Martiano, Vereki; Zaidi, Ahmad; Askhan, Asifa; Putra, Andika Bayu (Scoring: Journal of Film Music, 2025)
ABSTRACT  The film "Silogui" offers an authentic portrayal of children's lives on Siberut Island, Mentawai, West Sumatra, highlighting noble cultural values, reverence for nature, and the strong presence of ancestral spirits. The main narrative follows Kumey, who ventures to find Arenga palm wood with his friend, Aduy. Conflict arises when Kumey is disturbed by a great forest guardian spirit for failing to perform the Panki ritual. This incident leads Kumey to regret and promise to respect nature and ancestral customs. This journal specifically examines how musical illustration serves as the backbone of the narrative in "Silogui," analyzing how every note and rhythm not only accompanies but also actively shapes the cinematic experience, strengthening cultural themes, and deepening the emotions of the Mentawai child characters. Using a qualitative approach with semiotic analysis of music and film narrative, this research finds that music plays a crucial role in building atmosphere, representing spiritual values, and reinforcing messages of preservation.Keywords: Silogui, Kumey, Aduy,  Siberut, Mentawai, Panki